Problems in the Implementation of Independent Curriculum (IC) A Case Study at SMAN 1 Masbagik in Academic Year 2022/2023 - Aqila Nurfadila; Mahyuni Mahyuni; I Made Sujana; Arifuddin Arifuddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Independent Curriculum is an innovative learning approach that aims to encourage creativity, freedom of thought, and development of students potential. There are several problems such as lack of student involvement, lack of innovation and creativity and limitations in providing material. The Independent Curriculum appears as an alternative that provides a solution to this problem. This study aims to analyze the problems experienced by teachers in implementing the Independent Curriculum and its impact on teachers and students. The qualitative case study method was used to investigate the experiences of three English teachers and five student representatives from phase E using questionnaires, interviews, observations and documentation data collection methods. The results of the study found three main problems faced by teachers, namely the lack of training, support and facilities in the learning process, as well as challenges in designing learning tools. The impact felt by teachers due to these challenges included changes in teaching methods, increased pedagogical skills and knowledge, and increased motivation in teaching. While the impact felt by students includes the positive impact and negative impact of students. The positive impacts include increased involvement and motivation to learn, increased creativity and innovation, critical thinking skills, as well as collaboration and communication skills. However, the negative impacts that are felt include the lack of explanation from the teacher and some students feel too free, so they feel entitled to leave their learning obligations according to the curriculum. It can be interpreted that the impact of these problems affects the teaching and learning experience of teachers and students. To overcome these problems, it is necessary to make a comprehensive effort. Teachers need to receive adequate training to understand the concept and methodology of the Independent Curriculum and schools need to provide adequate learning facilities and infrastructure to support interactive and innovative learning.